ENERGY EFFICIENT SOLUTIONS FOR STEEL REFINING IN FOUNDRY CLASS ELECTRIC ARC FURNACE (Modern Problems of Metallurgy, 2023)
Analysis of recent research and publications. The technological period in foundry class electric arc furnaces (EAF) is usually long term, is determined by desulfurization of steel and accompanied by significant energy loss through emissive surface of shallow steelmaking bath. Known mathematical models of Sulphur removal do not take into attention the impact of hydrodynamics factors due to deepening of the steelmaking bath of the same volume. Purpose. The task is to show feasibility of energy savings in foundry class EAF due to implementation of “deep” bath with forced pneumatic mixing. Method. Numerical modeling of sulfur removal in the steelmaking bath under conditions of forced pneumatic mixing, Research findings. Mathematical model takes into account removal of sulfur on interfacial surface of thin steel film, covering gas bubbles, geometry of bath and two-phase region, hydrodynamics, coalescence of bubbles. Simulation showed that in a “deep” bath, having shape factor (diameter to depth ratio) 2.5, rate of desulfurization, increases up to 5-6.7 times compared with a standard not forcibly stirred bath with shape factor 4.5, due to amplification of mass transfer in two-phase region and film desulfurization, reaching at least 23-28 % in overall process. Rise of porous plug radius contributes to increase sulfur removal velocity due to enlargement of threshold flowrates, corresponding to transition bubble - jet mode and bath "breakdown” mode. Effect of bath deepening in overall improvement of desulfurization kinetics is on average 23%. Practical significance. The obtained results allow to expect a shortening of the technological period due to increase of sulfur removal processes by an average of 1.5 times. Taking into account the share of the technological period in the total duration of melting on average 25-30%, the reduction of melting time will be 8-10%, and the saving of electricity, with an average specific consumption in small-capacity arc furnaces of 850 kWh/t, is expected to be 60-70 kWh per ton of crude steel.
Keywords: arc steelmaking furnace; energy efficiency; “deep” bath; desulfurization; pneumatic stirring.